Biochemical studies on the relation of some hormones with blood glucose level - Dina Belal Abdelrheim; Samir Abdelmonem Ahmed; Sayed Abdelkader Sayed (Cairo : Dina Belal Abdelrheim, 2010)
Seventy six blood samples were taken from 66 volunteers (38 male and 28 female ) of type - 2 - diabetic patients and 10 samples from intact subjects . Serum samples were collected from the lab . New Kasr Elaini Teaching Hospital, Faculty of Medicine, Cairo University , Egypt . The age and adiponectin levels were measured at fasting and postprandial states
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Biochemistry
Issued also as CD
Keywords: Serum glucose; Serum insulin; Type - 2 - diabetic patients